Aurora A triggers Lgl cortical release during symmetric division to control planar spindle orientation - Carvalho, CA (2015)
Mitotic spindle orientation is essential to control cell-fate specification and epithelial architecture. The tumor suppressor Lgl localizes to the basolateral cortex of epithelial cells, where it acts together with Dlg and Scrib to organize apicobasal polarity. Dlg and Scrib also control planar spindle orientation, but how the organization of polarity complexes is adjusted to control symmetric division is largely unknown. Here, we show that the Dlg complex is remodeled during Drosophila follicular epithelium cell division, when Lgl is released to the cytoplasm. Lgl redistribution during epithelial mitosis is reminiscent of asymmetric cell division, where it is proposed that Aurora A promotes aPKC activation to control the localization of Lgl and cell-fate determinants. We show that Aurora A controls Lgl localization directly, triggering its cortical release at early prophase in both epithelial and S2 cells. This relies on double phosphorylation within the putative aPKC phosphorylation site, which is required and sufficient for Lgl cortical release during mitosis and can be achieved by a combination of aPKC and Aurora A activities. Cortical retention of Lgl disrupts planar spindle orientation, but only when Lgl mutants that can bind Dlg are expressed. Hence, our work reveals that Lgl mitotic cortical release is not specifically linked to the asymmetric segregation of fate determinants, and we propose that Aurora A activation breaks the Dlg/Lgl interaction to allow planar spindle orientation during symmetric division via the Pins (LGN)/Dlg pathway.